Visual Analytics to Support Industrial Vehicle Fleet Planning - Ferreira, Guilherme X.; de Paula, Melise Maria V.; Pagan, Rafael P.; Batista, Bruno G. (Proceedings / International Conference on Information Visualisation, 2021)
Data analytics is becoming more important due to the data generated by the immensity of systems driven by widespread use of internet and mobile devices. Getting useful information from a lot of data is a challenge that visual analytics can be an alternative to. Visual analytics promotes information visualization and data mining techniques to consolidate and extract insightful information from databases. This paper aims to apply visual analytics concepts to help new logistic solutions prospection for optimization of industrial vehicles fleet. As a result, an artifact prototype able to assess the fleet behavior in terms of operational and available vehicles was developed. The prototype was evaluated based on information visualization and visual analytics practices.